Impact of external demands problems on students’ psychological well-being: systematic literature review - Setiawan, Muhammad Andi; Estimurti, Endang Sri; Pantiwati, Yuni; Latipun, Latipun; Bulkani, Bulkani; In'am, Akhsanul; Hudha, Atok Miftachul (Institute of Advanced Engineering and Science, 2025)
Students’ well-being is often disturbed by external demands, such as academic pressure, family expectations, and social expectations. These demands can impact students’ mental and emotional well-being. This research aims to explore the problems of external demands for students’ psychological well-being. This research used the systematic literature review (SLR) method to investigate the impact of external demands on students’ psychological well-being. Data were collected from articles published between 2018 and 2023 from the Scopus database. Of the 93 articles, 26 articles were obtained after screening. Data mining and analysis were conducted with the help of Publish or Perish, Biblioshiny, and ATLAS.ti. The results show the complexity of external demands, with factors such as internal and external support, job control, social media use, and individual differences in emotion regulation playing essential roles. The long-term impacts of these demands can include increased levels of stress, anxiety, and depression in students. Therefore, it is essential to manage external demands strategically to create a learning environment that supports students’ psychological well-being. This research highlights the need for joint efforts between schools, families, and communities to address external demands on students. Effective interventions are needed to reduce the negative impact of external demands.